De uma cultura política à Teologia da Libertação: as cartas do cárcere de Frei Betto e a ditadura civil-militar no Brasil - Santos, Bruno Dias [UNESP] (2015)
The goal of this dissertation is to understand the historical process that preceded and inspired the works of liberation theology. Observe that the set of principles that formed the basis of the work of professional theologians and summarized their aspirations emerged and was taken over by a particular group of young people, even before they emerge. Thus, the personal experience of Friar Betto is taken as the object of this research, because he is one of the most notorious members of this group. Seeks to grasp how the cultural climate of the 1960's, coupled with changes in the Catholic Church and the political landscape in Latin America, generated over more than a decade, and through various training spaces, a key reading the real , even gathering a body of ideas that later based elaborations this current theological and social action of its militants. To do so, we analyzed approximately 208 letters written by the Dominican friar in the period in which he was imprisoned (1969-1973), whose in 2008 were collected in the book Letters from Prison 1969 to 1973